2020
DOI: 10.1029/2020jd033016
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐model Spread of the Changes in the East Asian Summer Monsoon System in CMIP5/6 Models

Abstract: The East Asian summer monsoon (EASM), impacting the lives of more than 1.5 billion people, is a complex climate system independent from the South Asia summer monsoon (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…Recently, Zhou et al (2020) conducted studies on the dynamical variability of the future projection of the EASM by using empirical-orthogonal-function analyses for the June-July-August averages. While their approach is useful to elucidate large-scale seasonal features, the present study highlights the usefulness of simple correlation analyses to elucidate local sub-seasonal features and to further investigate their mechanisms.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhou et al (2020) conducted studies on the dynamical variability of the future projection of the EASM by using empirical-orthogonal-function analyses for the June-July-August averages. While their approach is useful to elucidate large-scale seasonal features, the present study highlights the usefulness of simple correlation analyses to elucidate local sub-seasonal features and to further investigate their mechanisms.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As for the location, Seo et al (2013) showed that the multi-model ensemble-mean (MME) based on the Representative Concentration Pathway (RCP) 6.0 experiments of CMIP5 exhibited little meridional shift of EASM precipitation from the late twentieth century to the late twenty-first century. Possible future changes of the EASM are also investigated by many other studies (e.g., Li et al 2011;Freychet et al 2015;Chen and Bordoni 2016;Chen et al 2020;Zhou et al 2020;Jiang et al 2021;Endo et al 2021). A review is presented by Kitoh (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study regressed anomalies are calculated in each model rst and then are averaged across the models with equal weights, which is denoted as the MME. The inter-model consensus is considered as high if more than 70% of models agree on the sign of the MME (Jiang et The MV-EOF analysis can capture dominant patterns in the spatial phase relationships among several related variables, which favors physical insight into the interactive processes within a complex climate system (Wang 1992;Wang et al 2008a;Zhou et al 2019;Zhou et al 2020). In this study, the MME value of each variable is rst removed before the inter-model MV-EOF, and then each variable is standardized to coherent magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…In this study regressed anomalies are calculated in each model rst and then are averaged across the models with equal weights, which is denoted as the MME. The inter-model consensus is considered as high if more than 70% of models agree on the sign of the MME (Jiang et al The MV-EOF analysis can capture dominant patterns in the spatial phase relationships among several related variables, which favors physical insight into the interactive processes within a complex climate system (Wang 1992;Wang et al 2008a;Zhou et al 2019;Zhou et al 2020). In this study, the MME value of each variable is rst removed before the inter-model MV-EOF, and then each variable is standardized to coherent magnitude.…”
Section: Methodsmentioning
confidence: 99%